A Hairpin Electrochemical Aptasensor for Sensitive and Specific Detection of Thrombin Based on Homogenous Target Recognition. Issue 5 (21st March 2013) - Fu, Hu; Ge, Chuang; Cheng, Wei; Luo, Caihui; Zhang, Decai; Yan, Li; He, Yun; Yi, Gang
Abstract An electrochemical aptasensor was developed for sensitive and specific detection of thrombin by combining homogenous recognition strategy and gold nanoparticles (AuNPs) amplification. Streptavidin‐alkaline phosphatase was used as reporter molecule. Compared with the traditional hairpin aptasensor monitoring the distance of the redox molecule from the electrode surface, the proposed aptasensor successfully overcome the limitations of distance and improved the stability and high affinity of the aptamer hairpin through homogenous recognition, which enhanced the sensitivity and selectivity of the sensors effectively. Additionally, AuNPs were employed to increase the active area and conductivity of the electrode, thus, improving the sensitivity of the aptasensor. As a result, the designed thrombin detection sensor obtained a lower detection limit of 0.52 pM in buffer and 6.9 pM in blood serum.